The Largest Measles Outbreak, Including 38 Modified Measles and 22 Typical Measles Cases in Its Elimination Era in Yamagata, Japan, 2017 - Komabayashi, Kenichi; Seto, Junji; Tanaka, Shizuka; Suzuki, Yu; Ikeda, Tatsuya; Onuki, Noriko; Yamada, Keiko; Ahiko, Tadayuki; Ishikawa, Hitoshi; Mizuta, Katsumi (Japanese Journal of Infectious Diseases, 2018)
The incidence of modified measles (M-Me), characterized by milder symptoms than those of typical measles (T-Me), has been increasing in Japan. However, the outbreak dominated by M-Me cases has not been thoroughly investigated worldwide. The largest importation-related outbreak of measles with genotype D8 occurred in Yamagata Prefecture, Japan, from March to April 2017. This phenomenon was observed after Japan had achieved measles elimination in 2015. We confirmed 60 cases by detecting the genome of the measles virus (MeV). Among the cases, 38 were M-Me and 22 were T-Me. Thirty-nine (65.0%) patients were 20–39 years of age. Three out of 7 primary cases produced 50 transmissions, of which each patient caused 9–25 transmissions. These patients were 22–31 years old and were not vaccinated. Moreover, they developed T-Me and kept contact with the public during their symptomatic periods. Considering that M-Me is generally caused by vaccine failure, some individuals in Japan may have insufficient immunity for MeV. Accordingly, additional doses of measles vaccine may be necessary in preventing measles importation and endemicity among individuals aged 20–39 years. Furthermore, to accurately and promptly diagnose individuals with measles, particularly those who can be considered as primary cases, efforts must be exerted to detect all measles cases using epidemiological and genetic approaches in countries where measles elimination had been achieved.